Polymer solid electrolyte, preparation method thereof, diaphragm-free lithium secondary battery and lithium secondary battery
By introducing unsaturated ester monomers without carbon aromatic structure into the polymer substrate and performing in-situ polymerization, the problem of low ion conduction capacity at room temperature of the polymer solid electrolyte is solved, and the high ion conductivity and lithium ion mobility are improved, which enhances the cycle stability and safety performance of the battery.
Patent Information
- Application Number
- CN202411423853.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-05-02
AI Technical Summary
The low ion conduction capability of polymer solid electrolytes at room temperature limits their application in lithium-ion batteries.
Unsaturated ester monomers without carbon aromatic structure are introduced into the polymer substrate, and an ester polymer is formed by in-situ polymerization to improve ionic conductivity and lithium ion mobility.
The ionic conductivity and lithium ion mobility of polymer solid electrolytes are significantly improved, and the cycle stability and safety performance of the battery are enhanced.
Smart Images

Figure BDA0005081603370000031 
Figure BDA0005081603370000051 
Figure BDA0005081603370000121
Abstract
Description
Technical Field
[0001] The invention relates to a polymer solid electrolyte, a preparation method thereof, a diaphragm-free lithium secondary battery and a lithium secondary battery, belonging to the technical field of lithium ion batteries. Background Art
[0002] In order to achieve the strategic security and sustainable development of my country's new energy vehicle industry, solve the safety and endurance anxiety of existing new energy vehicles, seize the commanding heights of international solid-state battery technology, and put forward new challenges to the development of solid-state lithium-ion batteries. Among many technical routes (such as oxide solid electrolytes, sulfide solid electrolytes, polymer solid electrolytes, etc.), polymer solid electrolytes have the advantages of low cost, high processability, and environmental friendliness, and occupy an important position in the industrialization of high-energy-density all-solid-state batteries. However, common polymer solid electrolytes, such as PEO (polyethylene oxide) and PMMA (polymethyl methacrylate), have the disadvantages of high room temperature crystallinity and high glass transition temperature, which inhibit the movement of polymer chain segments, making the polymer lithium ion conductivity generally low, hindering its practical application.
[0003] The cell of an all-solid-state lithium battery is composed of solid electrodes and solid electrolyte materials. Within the operating temperature range, the cell does not contain any mass and volume fraction of liquid electrolyte. As the core component of an all-solid-state lithium battery, the solid electrolyte is the key material for preparing all-solid-state lithium batteries with high energy density, high cycle stability and high safety performance. Therefore, the development of a solid electrolyte with excellent performance has become the focus of researchers.
[0004] In order to improve the ionic conductivity of solid polymer electrolytes, they can usually be modified by introducing plasticizers or inorganic fillers, blending, grafting, copolymerization, etc.
[0005] Some documents disclose a solid electrolyte for a battery cell, which uses an acrylic polymer and a carbonate organic compound, but the acrylic polymer must be obtained by polymerization of two or more acrylic polymer monomers initiated by the initiator, and the carbonate organic compound must be added to the solid electrolyte.
[0006] Some documents disclose a composite solid polymer electrolyte prepared by mixing nano-ceramic particles, lithium-conducting polymers and lithium salts. The use of inorganic nanoparticles as composite solid polymer electrolyte fillers improves the ionic conductivity of the electrolyte itself, but the compatibility between the inorganic filler and the polymer matrix needs to be improved. The filler is prone to agglomeration in the polymer matrix, which affects the performance of the electrolyte.
[0007] In addition, for lithium-ion batteries, a diaphragm may or may not be used in its structure. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. In the case of using a diaphragm, the main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. In the case of not using a diaphragm, the positive and negative electrodes are usually separated by the electrolyte itself to prevent short-circuiting, and ions are conducted by the electrolyte itself. From the perspective of the energy density of lithium secondary batteries, secondary batteries without diaphragms are advantageous. In particular, the use of solid electrolytes (such as quasi-solid or all-solid electrolytes) makes diaphragm-free batteries possible.
[0008] It can be seen that although a series of studies have been conducted in this field on the improvement of polymer solid electrolytes, there is still room for further improvement in the development of polymer solid electrolytes that have high ionic conductivity, high lithium ion mobility and component compatibility. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] As mentioned above, polymer solid electrolytes have advantages such as good safety, however, their low ion conductivity at room temperature limits the development of polymer solid electrolytes. In order to enhance the room temperature ionic conductivity of polymer solid electrolytes, researchers have proposed methods such as introducing plasticizers, inorganic fillers, polymer blending, and copolymerization.
[0011] The introduction of plasticizers with high dielectric constants can promote the dissociation of lithium salts, but the introduction of plasticizers may lead to safety hazards. The compatibility between inorganic fillers and polymer matrices needs to be improved. They are prone to agglomeration in polymers, which in turn affects the lithium ion transmission channel. It is often necessary to introduce a large amount of organic solvents to make them evenly dispersed. However, the solvents are difficult to completely remove in the subsequent drying process, which will lead to a series of problems such as increased interface impedance, reduced cycle life, and poor safety during battery cycling.
[0012] However, methods such as blending and copolymerization in the prior art usually require the addition of multiple small molecules for polymerization to achieve the purpose of improving ionic conductivity. However, the addition of multiple small molecule monomers will make the structure and degree of polymerization after polymerization, the repeatability of the experiment, etc. more difficult to control and the cost is high.
[0013] Furthermore, as a previous research result of the applicant, in the Chinese patent application with application number 202410670877.5, in-situ polymerization is used to improve the performance of the final electrolyte. In this scheme, a monomer with the structure of the following formula (a) is used:
[0014]
[0015] Wherein, R1 and R2 are independently selected from H, a halogen atom or a substituted or unsubstituted hydrocarbon group; R3 represents a substituent group of the benzene ring, and each time R3 appears, it is independently selected from a hydrocarbon group or a polar group; m and n represent 0 or a positive integer, and m≥1, m+n=6; X represents a single bond or a divalent connecting group.
[0016] That is, in previous studies, unsaturated monomers formed by allyl alcohol and aromatic carboxylic acids were used as monomers for in-situ polymerization, which greatly improved the conductivity and cyclability.
[0017] Based on such results, it seems that unsaturated ester monomers show good properties. However, in further research, new problems are also found, that is, even if polymerizable monomers containing ester structures are used, especially monomers containing carbon aromatic structures, some of their effects are not always satisfactory.
[0018] This is mainly due to the presence of carbon aromatic structures, such as unsaturated esters containing benzene rings. In most cases, the polymer chain segment hardness is relatively high, which may lead to insufficient compatibility with the polymer matrix. In addition, when the hardness of the polymer chain segment is high, the mobility of the chain segment itself is also more inhibited, resulting in problems such as insufficient ion conductivity.
[0019] Therefore, for the desired improvement in performance, even with reference to the experience in application 202410670877.5, the type of monomer still needs to be selected very carefully.
[0020] In order to solve the above problems, the present invention provides a polymer solid electrolyte, which greatly improves the ionic conductivity and high lithium ion mobility by introducing an unsaturated ester monomer with a specific structure into a polymer matrix (such as PVDF, PEO, PMMA, PAN, etc.) and polymerizing it in situ in the polymer matrix. In addition, the unsaturated ester monomer structure of the present invention does not include a carbon aromatic structure, for example, does not include a benzene ring.
[0021] Furthermore, the present invention also provides a method for preparing a polymer solid electrolyte, through which the interfacial compatibility of the components in the polymer solid electrolyte can be improved, so that the prepared polymer solid electrolyte membrane can effectively suppress the problems caused by lithium dendrites and improve the cycle stability of the battery.
[0022] In addition, the present invention also provides a lithium secondary battery, which includes the polymer solid electrolyte described above or the polymer solid electrolyte prepared by the preparation method described above.
[0023] Solutions for solving problems
[0024] The present invention first provides a polymer solid electrolyte, wherein the polymer solid electrolyte comprises an ester polymer as component (A), a polymer substrate as component (B) and a lithium salt as component (C);
[0025] Wherein, the ester polymer includes structural units derived from unsaturated ester monomers;
[0026] The unsaturated ester monomer contains a carboxylate structure represented by the following formula (1) or a carbonate structure represented by (2):
[0027] -C(O)-O-(1)
[0028] -OC(O)-O-(2)
[0029] The component (A) is polymerized in situ in the solid electrolyte, and the unsaturated ester monomer structure does not contain a carbon aromatic structure.
[0030] According to the solid electrolyte of the present invention, the unsaturated ester monomer contains 1 to 3 unsaturated groups; and the carbon aromatic structure is a benzene ring.
[0031] According to the solid electrolyte of the present invention, the unsaturated group is an alkenyl group.
[0032] According to the solid electrolyte of the present invention, the monomer having the structure of formula (1) is selected from one or more of the following:
[0033] (1-a): carboxylate ester formed by monocarboxylic acid and monohydric alcohol;
[0034] (1-b): carboxylic acid esters formed by monocarboxylic acids and polyols;
[0035] (1-c): Carboxylate esters formed by polycarboxylic acids and monohydric alcohols.
[0036] According to the solid electrolyte of the present invention, the monocarboxylic acid or polycarboxylic acid is selected from substituted or unsubstituted aliphatic carboxylic acids, and / or the monohydric alcohol or polyhydric alcohol is selected from substituted or unsubstituted aliphatic alcohols.
[0037] According to the solid electrolyte of the present invention, the monomer having the structure of formula (2) is selected from one or more of the following cyclic carbonates having the structure of (2-a):
[0038]
[0039] The arc line represents the aliphatic structure.
[0040] R represents H or a substituent of the aliphatic structure.
[0041] According to the solid electrolyte of the present invention, the arc represents that the aliphatic structure is a substituted or unsubstituted aliphatic structure having 2 to 6 carbon atoms; and R is a substituted or unsubstituted aliphatic structure having 2 to 6 carbon atoms.
[0042] According to the solid electrolyte of the present invention, the mass ratio of component (A) to component (B) is 1:10 to 10:1.
[0043] According to the solid electrolyte of the present invention, the polymer substrate includes one or more combinations of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyethylene oxide, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyurethane, polyurea, polyvinyl pyrrolidone, polyvinyl chloride, polypropylene carbonate, polyimide, nylon, polyethylene terephthalate, poly-2-vinyl pyridine, and poly-4-vinyl pyridine.
[0044] According to the solid electrolyte of the present invention, the unsaturated ester monomer is selected from the group consisting of tetradecyl methacrylate, methyl oleate, hexyl methacrylate, sorbitol ester, isobutyl methacrylate, vinyl formate, vinyl acetate, vinyl propionate, vinyl hexanoate, trimethylvinyl acetate, vinyl n-butyrate, methacrylic acid ester, vinyl palmitate, vinyl stearate, diallyl maleate, ethylene glycol dimethacrylate, lauryl propionate, vinyl acrylate, vinyl ethylene carbonate or one or more combinations of vinyl carbonate.
[0045] In addition, the present invention also provides a method for preparing the polymer solid electrolyte according to the present invention, which comprises the following steps:
[0046] The polymer substrate, lithium salt, unsaturated ester monomer and initiator are mixed in an organic solvent to obtain a mixed solution;
[0047] The unsaturated ester monomer is polymerized.
[0048] According to the preparation method of the present invention, the mass ratio of the unsaturated ester monomer to the polymer substrate is 1:10 to 10:1;
[0049] The amount of the initiator is 0.01% to 1% by mass of the unsaturated ester monomer;
[0050] The amount of the lithium salt used is 10% to 70% by mass of the sum of the mass of the polymer substrate, the lithium salt, and the unsaturated ester monomer.
[0051] In addition, the present invention also provides a diaphragm-free lithium secondary battery, wherein the diaphragm-free lithium secondary battery comprises a positive electrode, a negative electrode, and comprises or uses the polymer solid electrolyte according to the present invention or the polymer solid electrolyte obtained by the preparation method according to the present invention.
[0052] Furthermore, the present invention also provides a lithium secondary battery, wherein the lithium secondary battery comprises a positive electrode, a negative electrode, a separator, and comprises or uses the polymer solid electrolyte according to the present invention or the polymer solid electrolyte obtained by the preparation method according to the present invention.
[0053] According to the lithium secondary battery of the present invention, the lithium secondary battery is an all-solid-state lithium battery.
[0054] Effects of the Invention
[0055] 1) The polymer solid electrolyte provided by the present invention introduces an ester polymer that does not contain a carbon aromatic structure. Its "ester" functional group has a synergistic effect with the existing functional groups in the polymer matrix, which can effectively improve the ionic conductivity of the polymer solid electrolyte. At the same time, the "carboxylate" or "carbonate" group is a polar functional group. Its introduction can enhance the ability to dissociate lithium salts, provide more free lithium ions, and improve lithium ion mobility;
[0056] 2) The unsaturated ester monomers from which the introduced ester polymers are derived are allowed to have one or more unsaturated carbon-carbon double bonds, which are conducive to the formation of a cross-linked structure and promote the interpenetrating network structure between the polymer substrate and the polymer chains formed by in-situ polymerization, thereby inhibiting the crystallization ability of the polymer molecular chain, enhancing the lithium ion transmission capacity, and further improving the ion conductivity.
[0057] 3) The preparation method of the polymer solid electrolyte provided by the present invention directly carries out in situ polymerization by adding unsaturated ester monomers that do not contain carbon aromatic structures into the polymer matrix solution, so that the two polymer molecular chains can be fully compatible and produce entanglement, which can improve the compatibility between the components of the polymer solid electrolyte, thereby inhibiting the crystallinity of the polymer solid electrolyte at room temperature, enhancing the movement of chain segments, and further improving the lithium ion transmission capacity and the cycle stability of the battery.
[0058] 4) The ester polymer of the present invention can be formed by polymerizing only one unsaturated ester monomer, which can bring convenience in operation and cost. DETAILED DESCRIPTION
[0059] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:
[0060] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0061] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0062] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0063] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0064] In this specification, the term "normal temperature" or "room temperature" refers to an indoor ambient temperature of "23±2°C".
[0065] In this specification, "plurality" is used to indicate a number of 2 or more.
[0066] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.
[0067] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.
[0068] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.
[0069] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0070] The present invention mainly provides a polymer solid electrolyte and a preparation method thereof, which greatly improves the ionic conductivity and high lithium ion mobility by introducing an ester polymer with a specific structure into a traditional polymer substrate.
[0071] The present invention is mainly obtained through the following insights:
[0072] In view of the problem of low ion conductivity of traditional polymer solid electrolytes, some research has been conducted on the improvement of polymer solid electrolytes in the prior art, such as by blending functional components or directly modifying the polymer electrolyte substrate. However, these methods often require the introduction of multiple small molecule compounds to improve different aspects of the problem. However, the addition of multiple small molecule monomers will make the structure and degree of polymerization after polymerization, the repeatability of the experiment, etc. more difficult to control and the cost is high.
[0073] Through the research of the present invention, it has been found that by introducing ester polymers formed by polymerization of unsaturated ester monomers that do not contain carbon aromatic structures into traditional polymer substrates, the ionic conductivity and high lithium ion mobility can be greatly improved, and there are no problems such as compatibility.
[0074] In addition, the present invention also discovered that in the preparation of polymer solid electrolytes, the adverse effects caused by interface compatibility have a great impact on the electrochemical stability of polymer solid electrolytes. Therefore, the present invention effectively improves the interface compatibility of each component in the polymer solid electrolyte by performing free radical polymerization in the polymer solid electrolyte solution, and due to the presence of the polymer substrate during the polymerization process, an interpenetrating network structure is formed between the polymerized ester polymer and the polymer substrate, thereby inhibiting the crystallinity of the polymer solid electrolyte at room temperature, enhancing chain segment movement, and further improving the lithium ion transmission capacity and the cycle stability of the battery.
[0075] <First aspect>
[0076] A first aspect of the present invention provides a polymer solid electrolyte comprising an ester polymer as component (A), a polymer base material as component (B), and a lithium salt as component (C).
[0077] In addition, various functional additive components may be used in the polymer solid electrolyte composition without hindering the realization of the technical effects of the present invention.
[0078] Component (A)
[0079] The ester polymer as component (A) of the present invention includes structural units derived from unsaturated ester monomers.
[0080] The ester monomers of the present invention can be selected from carboxylic acid ester monomers or carbonate monomers having the following structure (1) or (2):
[0081] -C(O)-O-(1)
[0082] -OC(O)-O-(2)
[0083] The above-mentioned ester monomers do not include a carbon aromatic structure in their structure. Meanwhile, in the present invention, one or a mixture of two or more different ester monomers may be used.
[0084] The carbon aromatic structure refers to an aromatic structure that is completely formed by carbon atoms, that is, all aromatic atoms are carbon atoms, typically, such as a benzene ring, a naphthalene ring, and the like.
[0085] In addition, for heteroaromatics (referring to the aromatic structure not entirely formed by carbon atoms, that is, all aromatic atoms can contain heteroatoms such as S, O, N, etc. in addition to carbon atoms), although due to certain polarity and other reasons, the effect is better than the case of monomers containing carbon aromatic structures, it is preferred that the unsaturated ester monomer structure of the present invention does not contain a heteroaromatic structure.
[0086] Furthermore, the unsaturation degree of the above-mentioned ester monomers can generally be 1 to 3, that is, for each unsaturated ester monomer, it can have 1 to 3 polymerizable / unsaturated groups, and such groups can preferably be free radical polymerizable double bonds (alkenyl groups).
[0087] Furthermore, the ester monomer having a carboxylate structure of the present invention may be selected from one or more of the following:
[0088] (1-a): carboxylate ester formed by monocarboxylic acid and monohydric alcohol;
[0089] (1-b): carboxylic acid esters formed by monocarboxylic acids and polyols;
[0090] (1-c): Carboxylate esters formed by polycarboxylic acids and monohydric alcohols.
[0091] Furthermore, these carboxylic acids or alcohols may be aliphatic, alicyclic, or heteroaromatic.
[0092] For the carboxylic acid ester represented by (1-a), wherein:
[0093] The monocarboxylic acid / monohydric alcohol may be selected from aliphatic, alicyclic or heteroaromatic carboxylic acids / alcohols having 1 to 20 carbon atoms, preferably 2 to 15 carbon atoms, more preferably 3 to 10 carbon atoms. Furthermore, the monocarboxylic acid / monohydric alcohol may or may not have an unsaturated group.
[0094] The aliphatic carboxylic acid / alcohol may have a straight chain structure or one or more branches, and may have an unsaturated group in the straight chain portion or the branched portion; the alicyclic carboxylic acid / alcohol may have one or more aliphatic rings, and may have an unsaturated group in the alicyclic portion or the non-cyclic portion.
[0095] (1-b): Carboxylic acid esters formed by monocarboxylic acids and polyols, wherein:
[0096] The monocarboxylic acid may be the same as defined above.
[0097] As for the polyol, in some preferred embodiments of the present invention, the polyol may be a 2-5-hydric alcohol, and more preferably the polyol may be a 2-hydric alcohol or a 3-hydric alcohol.
[0098] Furthermore, the polyol may be selected from aliphatic polyols, alicyclic polyols or heteroaromatic polyols having 1 to 20 carbon atoms, preferably, the carbon atoms may be 2 to 15, more preferably, the carbon atoms may be 3 to 10. In addition, the polyol may or may not have an unsaturated group. More preferably, the hydroxyl group in the polyol is located at the end of the molecular structure.
[0099] For the aliphatic polyol, it can be a straight chain structure or have one or more branches (comb-shaped or star-shaped), and it can have unsaturated groups in the straight chain part or the branched part; for the alicyclic polyol, it can have one or more aliphatic rings, and it can have unsaturated groups in the alicyclic part or the non-cyclic part.
[0100] (1-c): Carboxylic acid esters formed by polycarboxylic acids and monohydric alcohols, wherein:
[0101] The monohydric alcohol may be the same as the monohydric alcohol defined above.
[0102] As for the polycarboxylic acid, in some preferred embodiments of the present invention, the polycarboxylic acid may be a 2-5-valent carboxylic acid, and more preferably the polycarboxylic acid may be a 2- or 3-valent carboxylic acid.
[0103] Furthermore, the polycarboxylic acid may be selected from aliphatic polycarboxylic acids, alicyclic polycarboxylic acids or heteroaromatic polycarboxylic acids having 1 to 20 carbon atoms, preferably, the carbon atoms may be 2 to 15, more preferably, the carbon atoms may be 3 to 10. Furthermore, the polycarboxylic acid may or may not have an unsaturated group. More preferably, the carboxyl group in the polycarboxylic acid is located at the end of the molecular structure.
[0104] For the aliphatic polycarboxylic acid, it can be a straight chain structure or have one or more branches (comb-shaped or star-shaped), and it can have unsaturated groups in the straight chain part or the branched part; for the alicyclic polycarboxylic acid, it can have one or more aliphatic rings, and it can have unsaturated groups in the alicyclic part or the non-cyclic part.
[0105] In addition, the above-mentioned various carboxylic acids and alcohols may further have substituents. In principle, there is no particular limitation on such substituents, and it is also preferred that the substituents have appropriate polarity. Specifically, these substituents may include fluorine atoms.
[0106] In a further preferred embodiment of the present invention, from the perspective of compatibility, the above-mentioned carboxylic acid or alcohol monomer of the present invention may preferably be an ester monomer formed by a (straight chain / branched chain) aliphatic carboxylic acid and a (straight chain / branched chain) aliphatic alcohol.
[0107] For such carboxylic acid monomers, specific examples include: formic acid, acetic acid, (meth) acrylic acid, maleic acid, fumaric acid, C8-C20 (unsaturated) fatty acids, etc.;
[0108] Examples of such alcohol monomers include methanol, ethanol, ethylene glycol, vinyl alcohol, allyl alcohol, butenol, isobutenol, glycerol, propylene glycol, pentaerythritol, C8-C20 (unsaturated) fatty alcohols, etc. Preferably, the alcohol monomer is an alcohol monomer having 3 or more carbon atoms.
[0109] Further, the ester monomer having a carboxylate structure of the present invention may be selected from one or more of tetradecyl methacrylate (as shown in the following formula (1-1)), methyl oleate (as shown in the following formula (1-2)), hexyl methacrylate (as shown in the following formula (1-3)), sorbitol (as shown in the following formula (1-4)), isobutyl methacrylate, vinyl formate, vinyl acetate (as shown in the following formula (1-5)), vinyl propionate, vinyl hexanoate, trimethylacetic acid, vinyl n-butyrate, methacrylic alcohol acetate (as shown in the following formula (1-6)), vinyl palmitate, vinyl stearate, diallyl maleate (as shown in the following formula (1-7)), ethylene glycol dimethacrylate (as shown in the following formula (1-8)), lauryl propionate, vinyl acrylate, etc.:
[0110]
[0111] Further, the ester monomer having a carbonate structure of the present invention may be selected from one or more of the following in some preferred embodiments:
[0112]
[0113] The arc structure represents an aliphatic structure, and R represents H or a substituent on the aliphatic structure.
[0114] In some specific embodiments of the present invention, the arc-shaped structure represents a (straight chain / branched chain) aliphatic structure having 2 to 6 carbon atoms, preferably 2 to 4 carbon atoms, and such an aliphatic structure may also have a substituent, and such a substituent may preferably be a F atom.
[0115] For the R structure, in some specific embodiments, it can represent an aliphatic structure with 2 to 6 carbon atoms, preferably 2 to 4 carbon atoms. Similarly, such an aliphatic structure can also have a substituent, and such a substituent can preferably be a F atom.
[0116] In some preferred embodiments of the present invention, the ester monomer having a carbonate structure may be selected from one or more of the following structures:
[0117]
[0118] Wherein R1 represents an unsaturated structure having 2 to 3 carbon atoms, and R2 represents hydrogen or a saturated structure having 2 to 3 carbon atoms.
[0119] In some more preferred embodiments of the present invention, the ester monomer having a carbonate structure may be selected from one or more of the structures of vinyl ethylene carbonate (as shown in the following formula (2-1)) or vinylene carbonate (as shown in the following formula (2-2)):
[0120]
[0121] In addition, in addition to the above-mentioned unsaturated ester monomers, other unsaturated monomers can also be used in component (A) of the present invention. When other unsaturated monomers are used, these monomers account for less than 10% by mass of the total mass of all monomers, preferably less than 8% by mass, and more preferably less than 5% by mass.
[0122] In some specific embodiments, the degree of polymerization of the ester polymer of component (A) in the polymer solid electrolyte is not particularly limited in principle, and can be controlled by the relative amount of the initiator to obtain a suitable degree of polymerization.
[0123] Component (B)
[0124] The polymer substrate as component (B) described in the present invention is provided as a base material.
[0125] The type of polymer substrate may be a high molecular polymer material, which generally has a higher dielectric constant and can make the lithium salt described below ionized better.
[0126] In some specific embodiments of the present invention, such a polymer substrate can be selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polyethylene oxide (PEO), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer (PVDF-TrFE-CTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyurethane (PU), polyurea (PUA), polyvinyl pyrrolidone (PVP), polyvinyl chloride (PVC), polypropylene carbonate (PPC), polyimide, nylon, polyethylene terephthalate, poly2-vinylpyridine, poly4-vinylpyridine, etc.
[0127] Component (C)
[0128] The lithium salt as component (C) described in the present invention is the source of active ions in the polymer solid electrolyte and is itself included in the polymer solid electrolyte system. Without the lithium salt, the polymer solid electrolyte will lose the function of conducting active ions and the entire battery will not work.
[0129] Regarding the type of lithium salt, in some specific embodiments of the present invention, the lithium salt can be selected from one or more salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2 - 、C(CF2SO2)3 - 、C2BF2O4 - Preferably, the lithium salt may be lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0130] Polymer solid electrolyte composition
[0131] Regarding the composition of the polymer solid electrolyte of the present invention, from the aspect of improving the electrical properties of the electrolyte, the contents of the various components of the present invention can be arranged as follows:
[0132] Regarding the content of component (A), the mass ratio of component (A) to component (B) is 1:10 to 10:1, preferably 1:3 to 3:1, for example, 1:5, 1:1, 2:1, 5:1, 8:1, etc. When the content of component (A) is too low, the interaction between functional groups may be weak, and the improvement effect on inhibiting crystallization may be limited; when the content of component (A) is too high, the mechanical properties of the film may deteriorate, or even the film may not be formed, and the processability may be poor.
[0133] In principle, there is no particular restriction on the content of component (C), and it can be carried out in accordance with the general specifications of the amount of lithium salt in the art. In some specific embodiments, the content of component (C) is 10% to 70% by mass of the total mass of the polymer solid electrolyte, preferably 20% to 40% by mass, such as 15% by mass, 25% by mass, 35% by mass, 45% by mass, 55% by mass, 65% by mass, etc. When the content of component (C) is too low, there may be a risk of reducing the lithium ion transmission capacity; when the content of component (C) is too high, it may affect the mechanical properties of the polymer solid electrolyte.
[0134] The (usage) form of polymer solid electrolyte
[0135] Regarding the form of the polymer solid electrolyte of the present invention, in some specific embodiments, the above-mentioned polymer solid electrolyte composition can be provided separately, and such a composition can be prepared into a film material for use.
[0136] The solid electrolyte of the present invention contains substantially no organic solvent or (other) liquid components.
[0137] <Second Aspect>
[0138] The second aspect of the present invention provides a method for preparing the polymer solid electrolyte described in the first aspect.
[0139] The preparation method of the present invention mainly comprises:
[0140] The polymer substrate, lithium salt, unsaturated ester monomer and initiator are mixed in an organic solvent to obtain a mixed solution;
[0141] The unsaturated ester monomer is polymerized.
[0142] The types and amounts of the polymer substrate, lithium salt, and unsaturated ester monomer are the same as those in the first aspect and will not be described in detail herein.
[0143] The initiator described in the present invention is a free radical initiator, which is used to cause the unsaturated ester monomer to undergo free radical polymerization in the polymer matrix to form a cross-linked network.
[0144] The free radical initiator can be a thermal initiator or a photoinitiator.
[0145] The type of thermal initiator may be selected from one or more of azo initiators, organic peroxide initiators and the like.
[0146] In some specific embodiments, the thermal initiator may include one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, dibenzoyl peroxide, diethylhexyl peroxydicarbonate, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxycarbonate, potassium persulfate, or ammonium persulfate.
[0147] The type of photoinitiator can be selected from one or more of the cleavage type or the hydrogen abstraction type. In some specific embodiments, the cleavage type can be selected from one or more of benzoin and its derivatives, acetophenones, aromatic ketones and acylphosphine oxides; the hydrogen abstraction type initiator can be selected from one or more of benzophenone, thioxanthone, camphor porquinone and bisimidazole.
[0148] Regarding the amount of the initiator added, the amount of the initiator added is 0.01% to 1% by mass of the unsaturated ester monomer, for example, it can be 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9% by mass, etc.
[0149] As for the type of organic solvent, for example, it can be selected from at least one of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0150] In some specific embodiments, in the mixing step, in order to achieve the migration of lithium ions, the polymer substrate and the lithium salt can be first mixed with the organic solvent and stirred thoroughly until dissolved to dissociate the lithium salt, and then the unsaturated ester monomer and the initiator can be added.
[0151] In addition, the polymerization reaction can be controlled by, for example, irradiating or heating the polymerization reaction. In some preferred embodiments, heating can be used to cause the polymerization reaction to occur.
[0152] There is no particular limitation on the reaction temperature, and the required reaction temperature can be adopted according to the type of initiator. In some preferred embodiments, the reaction temperature can be 40 to 70°C, such as 45°C, 50°C, 55°C, 60°C, 65°C, etc.; the reaction time can be 4 to 18 hours, such as 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.
[0153] In some more specific embodiments, the reaction can be carried out under inert gas conditions, such as argon, etc. For example, after the mixing step, an inert gas can be introduced into the mixed solution to expel the air dissolved in the solvent and in the reaction container, and then the mixture is sealed.
[0154] In some specific embodiments, the preparation method further comprises a film-forming step, and the film-forming method may be a solution coating method, an extrusion casting method or the like.
[0155] In some more specific embodiments, the solution coating method includes applying the solution to a substrate and drying it, removing the substrate, thereby obtaining a film-like polymer solid electrolyte. There is no particular limitation on the substrate, for example, it can be a glass substrate, a ceramic substrate, a stainless steel substrate, a plastic substrate, etc. For the drying temperature and time, for example, it can be dried in a vacuum drying oven at 50 to 100°C, preferably 60 to 80°C for 4 to 10 hours, preferably 4 to 8 hours. After drying, a thin film on the substrate can be obtained. Peeling the film off the substrate (i.e., removing the substrate) can obtain a film-like polymer solid electrolyte. In addition, the obtained film-like polymer solid electrolyte can also be cut into a suitable shape and size as needed, for example, it can be cut into a circular electrolyte sheet of Φ16mm.
[0156] The preparation method of the present invention has many advantages such as low cost, simple method, environmental friendliness, and high safety of the prepared polymer solid electrolyte, and has extremely broad prospects in practical application.
[0157] <Third Aspect>
[0158] The third aspect of the present invention provides a lithium secondary battery, in particular a lithium secondary battery comprising or using the polymer solid electrolyte described in the first aspect of the present invention or a polymer solid electrolyte prepared according to the preparation method described in the second aspect.
[0159] Such a lithium secondary battery at least includes a positive electrode, a negative electrode and a solid electrolyte. In addition, a diaphragm can be used when necessary. In some specific embodiments, a diaphragm is further used in the lithium secondary battery. There is no particular restriction on such a diaphragm, and an organic porous membrane can be used. In some other specific embodiments, the lithium secondary battery is a diaphragm-free lithium secondary battery. Preferably, the lithium secondary battery can be an all-solid-state battery, which is allowed to not contain a liquid electrolyte and a diaphragm, and relies on a solid electrolyte to isolate the positive and negative electrodes and transmit lithium ions.
[0160] In addition, in some preferred embodiments, the positive electrode active material in the positive electrode can be an electrode active material containing nickel element; and the negative electrode is a metallic lithium negative electrode.
[0161] Example
[0162] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0163] Example 1
[0164] (1) Preparation of polymer solid electrolyte solution:
[0165] 4 g of PEO, 4 g of lithium bis(trifluoromethanesulfonyl)imide (equivalent to 50% of the total mass of all polymers after polymerization) and 0.02 g of AIBN were dissolved in 30 ml of DMF and stirred magnetically until dissolved. 4 g of vinyl acetate was added and the mixture was mixed for 30 min. An inert gas was introduced for 30 min to expel the air in the container and the mixture was heated and stirred at 65° C. for 4 h.
[0166] (2) Preparation of composite solid polymer electrolyte membrane:
[0167] The mixed solution prepared above was poured onto a clean glass plate and dried in a vacuum drying oven at 80°C for 8 hours using a solution coating method. The film was then peeled off the glass plate and cut into a Φ16 mm circular polymer solid electrolyte membrane.
[0168] The polymer solid electrolyte membrane prepared as described above was used to carry out battery assembly and testing, and the ionic conductivity and cycle stability were obtained, as shown in Table 1.
[0169] Example 2
[0170] The difference from Example 1 is that PEO is replaced by PVDF-HFP, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is made, and a battery is assembled and then subsequent tests are carried out, as shown in Table 1.
[0171] Example 3
[0172] The difference from Example 1 is that PEO is replaced by PU, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0173] Example 4
[0174] The difference from Example 1 is that PEO is replaced by PVDF, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0175] Example 5
[0176] The difference from Example 1 is that the amount of vinyl acetate added is 2 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0177] Example 6
[0178] The difference from Example 1 is that the amount of vinyl acetate added is 3 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0179] Example 7
[0180] The difference from Example 1 is that the amount of vinyl acetate added is 5 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0181] Example 8
[0182] The difference from Example 1 is that the amount of vinyl acetate added is 6 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0183] Comparative Example 1
[0184] The difference from Example 1 is that the mixed solution is not heated, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing, as shown in Table 1.
[0185] Comparative Example 2
[0186] The difference from Example 1 is that no unsaturated ester monomer and initiator are added, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0187] Comparative Example 3
[0188] The difference from Example 1 is that the unsaturated ester monomer added is allyl benzoate, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled for subsequent testing. The details are shown in Table 1.
[0189] Performance Testing
[0190] 1. Ionic conductivity: The prepared polymer solid electrolyte sheet (CSEs) and two stainless steel electrodes (SS) are combined to form a SS / CSEs / SS simulated battery for testing. The battery assembly process is carried out in a glove box with a water and oxygen content of less than 0.1ppm. The electrochemical impedance spectroscopy (EIS) test uses a frequency range of 0.01Hz to 106Hz to measure the electrochemical impedance of the polymer solid electrolyte at room temperature. The impedance data obtained from the EIS test is used to calculate the ionic conductivity of the prepared polymer solid electrolyte.
[0191] 2. Cycling performance: The prepared polymer solid electrolyte sheets (CSEs) were combined with lithium iron phosphate (LiFePO4) positive electrodes and lithium metal negative electrodes to form button cells. The preparation of the cells was carried out in a glove box. The cells were tested for charge and discharge cycles at a rate of 0.5C, and the attenuation of their discharge capacity was detected.
[0192] Table 1 Performance test results of embodiments and comparative examples
[0193]
[0194] Note: * indicates that the attenuation during the test is severe and has no measurement significance.
[0195] The results of Examples 1, 5-8 and Comparative Example 2 show that the introduction of ester polymers can effectively improve the ionic conductivity of the polymer solid electrolyte, and after being assembled into button cells, its cycle stability is effectively improved.
[0196] The results of Examples 1-4 show that ester polymers are compatible with different polymer substrates and exhibit high ionic conductivity and cycle stability.
[0197] The results of Example 1 and Comparative Example 1 show that if only unsaturated ester monomers are added without initiating polymerization, the electrochemical properties of the polymer solid electrolyte cannot be significantly improved, and the liquid monomers will significantly reduce the mechanical properties of the polymer solid electrolyte, resulting in its inability to form a film.
[0198] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0199] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A polymer solid electrolyte, characterized in that: The polymer solid electrolyte comprises an ester polymer as component (A), a polymer substrate as component (B), and a lithium salt as component (C); Wherein, the ester polymer includes structural units derived from unsaturated ester monomers; The unsaturated ester monomer contains a carboxylate structure represented by the following formula (1) or a carbonate structure represented by (2): -C(O)-O-(1) -OC(O)-O-(2) The component (A) is polymerized in situ in the solid electrolyte, The unsaturated ester monomer structure does not contain a carbon aromatic structure.
2. The solid electrolyte according to claim 1, characterized in that The unsaturated ester monomer contains 1 to 3 unsaturated groups; the carbon aromatic structure is a benzene ring.
3. The solid electrolyte according to claim 2, characterized in that The unsaturated group is an alkenyl group.
4. The solid electrolyte according to any one of claims 1 to 3, characterized in that The monomer having the structure of formula (1) is selected from one or more of the following: (1-a): carboxylate ester formed by monocarboxylic acid and monohydric alcohol; (1-b): carboxylic acid esters formed by monocarboxylic acids and polyols; (1-c): Carboxylate esters formed by polycarboxylic acids and monohydric alcohols.
5. The solid electrolyte according to claim 4, characterized in that The monocarboxylic acid or polycarboxylic acid is selected from substituted or unsubstituted aliphatic carboxylic acids, and / or the monohydric alcohol or polyhydric alcohol is selected from substituted or unsubstituted aliphatic alcohols.
6. The solid electrolyte according to any one of claims 1 to 5, characterized in that: The monomer having the structure of formula (2) is selected from one or more of the following cyclic carbonates having the structure of (2-a): The arc line represents the aliphatic structure. R represents H or a substituent of the aliphatic structure.
7. The solid electrolyte according to claim 6, characterized in that The arc indicates that the aliphatic structure is a substituted or unsubstituted aliphatic structure having 2 to 6 carbon atoms; and R is a substituted or unsubstituted aliphatic structure having 2 to 6 carbon atoms.
8. The solid electrolyte according to any one of claims 1 to 7, characterized in that: The mass ratio of the component (A) to the component (B) is 1:10 to 10:
1.
9. The solid electrolyte according to any one of claims 1 to 8, characterized in that: The polymer substrate includes one or more combinations of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polyethylene oxide, polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyurethane, polyurea, polyvinyl pyrrolidone, polyvinyl chloride, polypropylene carbonate, polyimide, nylon, polyethylene terephthalate, poly2-vinyl pyridine, and poly4-vinyl pyridine.
10. The solid electrolyte according to any one of claims 1 to 9, characterized in that: The unsaturated ester monomer is selected from the group consisting of tetradecyl methacrylate, methyl oleate, hexyl methacrylate, sorbitol ester, isobutyl methacrylate, vinyl formate, vinyl acetate, vinyl propionate, vinyl hexanoate, trimethylvinyl acetate, vinyl n-butyrate, methacrylic alcohol acetate, vinyl palmitate, vinyl stearate, diallyl maleate, ethylene glycol dimethacrylate, lauryl propionate, vinyl acrylate, vinyl ethylene carbonate, or a combination of one or more of vinyl carbonate.
11. A method for preparing a polymer solid electrolyte according to any one of claims 1 to 10, characterized in that: The following steps are involved: The polymer substrate, lithium salt, unsaturated ester monomer and initiator are mixed in an organic solvent to obtain a mixed solution; The unsaturated ester monomer is polymerized.
12. The preparation method according to claim 11, characterized in that: The mass ratio of the unsaturated ester monomer to the polymer substrate is 1:10 to 10:1; The amount of the initiator is 0.01% to 1% by mass of the unsaturated ester monomer; The amount of the lithium salt used is 10% to 70% by mass of the sum of the mass of the polymer substrate, the lithium salt, and the unsaturated ester monomer.
13. A diaphragm-free lithium secondary battery, characterized in that: The separator-free lithium secondary battery comprises a positive electrode, a negative electrode and comprises or uses the polymer solid electrolyte according to any one of claims 1 to 10 or the polymer solid electrolyte obtained by the preparation method according to claim 11 or 12.
14. A lithium secondary battery, characterized in that: The lithium secondary battery comprises a positive electrode, a negative electrode, a separator and comprises or uses the polymer solid electrolyte according to any one of claims 1 to 10 or the polymer solid electrolyte obtained by the preparation method according to claim 11 or 12.
15. The lithium secondary battery according to claim 14, characterized in that: The lithium secondary battery is an all-solid-state lithium battery.
Citation Information
Patent Citations
Polymer solid electrolyte, preparation method thereof and battery
CN118630308A